2020
DOI: 10.1074/jbc.ra119.012145
|View full text |Cite
|
Sign up to set email alerts
|

AIG1 and ADTRP are endogenous hydrolases of fatty acid esters of hydroxy fatty acids (FAHFAs) in mice

Abstract: Keywords: fatty acid ester of hydroxy fatty acid (FAHFA), threonine hydrolase, metabolism, androgeninduced gene 1(AIG1), androgen-dependent TFPI-regulating protein (ADTRP), lipid ester, enzyme inhibitor, diabetes, lipid signaling, glucose metabolism. AbstractFatty acid esters of hydroxy fatty acids (FAHFAs) are a newly discovered class of signaling lipids with anti-inflammatory and antidiabetic properties. However, the endogenous regulation of FAHFAs remains a pressing but unanswered question. Here, using MS-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 53 publications
4
34
0
Order By: Relevance
“…The mRNA expression of Adtrp increased significantly (3–4 times) during embryogenesis [ 39 ]. Another group also reported localization of mouse ADTRP in the liver, adipose tissue, kidney, and duodenum [ 40 ].…”
Section: Structure Expression and Tissue Localization Of Adtrpmentioning
confidence: 99%
See 4 more Smart Citations
“…The mRNA expression of Adtrp increased significantly (3–4 times) during embryogenesis [ 39 ]. Another group also reported localization of mouse ADTRP in the liver, adipose tissue, kidney, and duodenum [ 40 ].…”
Section: Structure Expression and Tissue Localization Of Adtrpmentioning
confidence: 99%
“…Neo-/perinatal mortality of ~35% in Adtrp −/− mice correlated with the degree of phenotype severity. In independently generated Adtrp mutant mice, another group [ 40 ] found that mice lacking ADTRP developed normally with the expected Mendelian ratio. The discrepancy between our mice and theirs can be attributed to different strategies applied to generate ADTRP-deficient mice.…”
Section: Role Of Adtrp In Cardiovascular Health and Diseasementioning
confidence: 99%
See 3 more Smart Citations